The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14739879.2016.1266239
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of experiences and views of Scottish leadership training opportunities amongst primary care professionals

Abstract: Leadership is key to improve quality, safety and efficiency of care and help deliver innovative services and transformative change. To date, leadership provision for primary care professionals has typically been patchy, uni-disciplinary in focus and undertaken outwith work environments. Future development must reflect needs of busy primary care professionals and the reality of team working to deliver integrated services at local level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…25 A survey of primary care professionals in Scotland found fewer than half had previous leadership training, and among nurses, less than 30% had such training. 26 Nevertheless, there are documented examples of primary care practices that do have engaged leaders who have successfully transitioned practices into advanced PCMH models despite challenges. 20,27,28 Over the past 30 years, two of the authors (WLM and BFC) actively engaged in a program of research that included hundreds of primary care practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 A survey of primary care professionals in Scotland found fewer than half had previous leadership training, and among nurses, less than 30% had such training. 26 Nevertheless, there are documented examples of primary care practices that do have engaged leaders who have successfully transitioned practices into advanced PCMH models despite challenges. 20,27,28 Over the past 30 years, two of the authors (WLM and BFC) actively engaged in a program of research that included hundreds of primary care practices.…”
mentioning
confidence: 99%
“…A recent focus group study in Norway found that while general practitioners recognized the need to take on leadership roles, they did not have the leadership skills and training needed to effectively lead their teams 25 . A survey of primary care professionals in Scotland found fewer than half had previous leadership training, and among nurses, less than 30% had such training 26 . Nevertheless, there are documented examples of primary care practices that do have engaged leaders who have successfully transitioned practices into advanced PCMH models despite challenges 20,27,28 …”
mentioning
confidence: 99%
“…The uptake of leadership skills training is suboptimal, a gulf of leadership skills development commonly opens up early in the career of most Scottish pharmacists, and many struggle to implement leadership skills in day-to-day practice. [56][57][58] Pharmacists identify that they do not understand the common vision and purpose of their teams. 56 Pharmacists also commonly identify a training gap in their skills of population-level care delivery.…”
Section: The 'Atomistic' Modelmentioning
confidence: 99%